A validation of the religious and spiritual struggles scale among young people living with HIV in Zimbabwe: Mokken scale analysis and exploratory factor analysis - Wüthrich-Grossenbacher, Ursula; Mutsinze, Abigail; Wolf, Ursula; Maponga, Charles Chiedza; Midzi, Nicholas; Mutsaka-Makuvaza, Masceline Jenipher; Merten, Sonja (Frontiers in Psychology, 2023)
Religious/spiritual convictions and practices can influence health and treatment seeking behavior, but only few measures of religiousness or spirituality have been validated outside of the US. The Religious and Spiritual Struggles scale (RSS) measures internal and external conflict with religion and spirituality and has been validated mainly in different high-income contexts. The aim of this study was the validation of the RSS in the Zimbabwean context and among young people living with Human Immunodeficiency Virus aged 14-24. Data collection with an Open Data Kit questionnaire with 804 respondents took place in 2021. The validation was done by Confirmatory Factor Analysis using Statistical Equation Modelling, and Mokken Scale Analysis. After low confirmability of the original scale sub-dimensions Exploratory Factor Analysis was applied, resulting in four new sub-domains, different from the original six domains in the RSS, but culturally more relevant. The new sub-domains are significantly related to health. The findings support the validity and relevance of the RSS and the new sub-domains in this context. As our study was limited to young people living with Human Immunodeficiency Virus, further validation of the RSS among different population groups and contexts in the sub-Saharan region are encouraged.